Cement-based adhesive for geopolymers, geopolymers and use thereof

By using a variety of cement-based adhesives that combine chemically different aluminosilicates with Portland cement, etc., in geopolymers, the shortcomings in adhesion and shrinkage of geopolymers are solved, and high Compressive strength and chemical corrosion resistance.

CN119486985APending Publication Date: 2025-02-18SIKA TECH AG
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380051668.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-15
Filing Date
2023-07-03
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing geopolymers have poor adhesion to aggregates or steel bars and have a high shrinkage rate, making it difficult to take into account the characteristics of chemical corrosion resistance and low shrinkage rate.

Method used

Optimize chemical erosion resistance through specific weight ratio combinations using cement-based adhesives containing at least two chemically different aluminosilicates, Portland cement, calcium sulfaluminate cement or calcium aluminate cement and calcium sulfate sources. Sex and contraction behavior.

Benefits of technology

The low autogenous or chemical shrinkage of geopolymers, high compressive strength after hardening, good chemical corrosion resistance and high freeze-thaw resistance are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119486985A_ABST
    Figure CN119486985A_ABST
Patent Text Reader

Abstract

The invention relates to a binder for geopolymers, comprising a) not less than 30 wt% of a mixture of at least two chemically different aluminosilicates, b) not less than 20 wt% of a common Portland cement, and c) 8-20 wt% of a calcium sulphoaluminate cement or a mixture of a calcium aluminate cement and a calcium sulfate source, the weight ratio of calcium sulfate to calcium sulphoaluminate and / or calcium aluminate is 0.08-1.5, preferably 0.3-1.1, and more preferably 0.6-1.1. The invention also relates to geopolymers using such adhesives and to the use thereof in various construction methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a binder for geopolymers, the binder comprising at least two chemically different aluminosilicates, Portland cement, calcium sulfoaluminate cement or calcium aluminate cement and a source of calcium sulfate. The invention also relates to geopolymers using such a binder and their use in various construction methods. Background of the Invention

[0003] As is well known, geopolymers are an alternative to Portland cement-based building materials. The term "geopolymer" was first used by Joseph Davidovits, and corresponding materials were proposed as early as 1981 (for example, see EP0026687 by J. Davidovits and CORDIS). In it, alkaline silicate solutions react with silicon and aluminum in source materials of geological origin or by-product materials (such as fly ash) to form adhesives. Since the chemical reaction that occurs is a polymerization process, the term "geopolymer" is used for these adhesives. Thereafter, geopolymers generally consist of an aluminum silicate component and an alkali metal silicate component, which react with each other in a geopolymerization reaction. The aluminum silicate components used include fly ash, slag and metakaolin.

[0004] Geopolymers are considered environmentally friendly building materials because the production of their starting materials produces much less CO2 than the production of Portland cement.

[0005] Geopolymer compositions, in particular geopolymer adhesives, are described in many publications. For example, US 2011 / 0271876 (S. Alter et al.) discloses geopolymer compositions based on a mixture of blast furnace slag with bauxite, alumina slag or tailings and activated by alkaline silicates.

[0006] Geopolymers can exhibit rapid solidification and hardening properties and have high compressive strength in the cured state. In addition, geopolymers are reported to have good resistance to chemical erosion (e.g., see HJ Zhuang et al., "Resistance of geopolymer mortarto acid and chloride attacks", Procedia Engineering, 2017, No. 210, pp. 126-131).

[0007] However, there are also reports that geopolymers have poor adhesion to materials such as aggregates or reinforcement. In addition, geopolymers generally have a higher shrinkage than Portland cement-based building materials. In view of this, geopolymer compositions with low shrinkage have been developed, such as disclosed in WO 2013 / 163009 (American Gypsum Company). This WO 2013 / 163009 discloses a geopolymer composition comprising a thermally activated aluminosilicate mineral, a calcium sulfoaluminate cement and a calcium sulfate source as a binder activated with an alkali metal salt and / or an alkali metal base.

[0008] There is still a need for compositions that combine some of the advantages of geopolymers (such as high resistance to chemical attack) with some of the advantages of Portland cement-based binders (such as low shrinkage). Therefore, the present invention provides new cement-based binders and geopolymers for geopolymers to meet this need. SUMMARY OF THE INVENTION

[0010] One object of the present invention is to provide a cement-based binder for geopolymers. Another object of the present invention is to provide a geopolymer composition using such a cement-based binder. In particular, the cement-based binder for geopolymers, and therefore the geopolymer composition using these cement-based binders, also has one or more of the following characteristics:

[0011] (i) low autogenous or chemical shrinkage during hardening,

[0012] (ii) High compressive strength after hardening,

[0013] (iii) high resistance in the hardened state to chemical attack, in particular to attack by acids, sulfates, chlorides and / or salt water,

[0014] (iv) High freeze-thaw resistance in the hardened state.

[0015] Surprisingly, it has been found that combinations of Portland cement with at least two chemically different aluminosilicates, and also combinations with calcium sulphoaluminate cement or mixtures of calcium aluminate cement and calcium sulphate, are suitable for cement-based binders for geopolymers with the above-mentioned advantages.

[0016] In particular, it has been found that combining at least two chemically different aluminosilicates with Portland cement results in improved chemical resistance, particularly acid resistance, of the cured composition. Combining two chemically different aluminosilicates with Portland cement results in higher chemical resistance than using each aluminosilicate alone.

[0017] It has likewise surprisingly been found that the chemical resistance and the shrinkage behavior are optimized by the additional use of calcium sulphoaluminate and / or a mixture of calcium aluminate and a calcium sulphate source in a specific weight ratio.

[0018] Therefore, the object of the present invention is solved by a cement-based binder for geopolymer compositions as claimed in claim 1.

[0019] Further aspects of the invention are the subject matter of the independent claims. Preferred embodiments are the subject matter of the dependent claims.

[0020] Mode for carrying out the invention

[0021] In a first aspect, the present invention relates to a cementitious binder for geopolymers, said cementitious binder comprising (in each case relative to the total dry weight of the cementitious binder)

[0022] a) not less than 30 wt. % of a mixture of at least two chemically different aluminosilicates,

[0023] b) not less than 20 wt% of ordinary Portland cement, and

[0024] c) 8-20 wt% of calcium sulfoaluminate cement or a mixture of calcium aluminate cement and a calcium sulfate source, wherein in the mixture, the weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is between 0.08-1.5, preferably 0.3-1.1, more preferably 0.6-1.1.

[0025] In this article, aluminosilicate refers to a material with pozzolanic and / or potential hydraulic properties of aluminosilicate as a component. The chemical composition of aluminosilicate can be measured by XRF according to the description in EN 196-2:2013 standard. Aluminosilicate of the present invention is mainly composed of silicon dioxide (SiO2 or "S" in cement chemical symbols), aluminum oxide (Al2O3 or "A" in cement chemical symbols), calcium oxide (CaO or "C" in cement chemical symbols), iron oxide (Fe2O3 or "F" in cement chemical symbols) and a small amount of magnesium oxide (MgO), sulfur dioxide (SO3) ("$" in cement chemical symbols), titanium oxide (TiO2), phosphorus oxide (P2O5), sodium oxide (Na2O), potassium oxide (K2O) One or more constitute, as determined by XRF analysis.

[0026] Examples of aluminosilicates according to the invention are steelmaking slag, fly ash of Class F according to ASTM C618, clay minerals, in particular calcined clay, glassy pumice, glassy volcanic ash, zeolite tuff, diatomaceous earth, burnt oil shale and organic combustion residues. According to a preferred embodiment, the first aluminosilicate is steelmaking slag and the other aluminosilicates are selected from fly ash of Class F according to ASTM C618 and / or calcined clay.

[0027] In this context, steelmaking slag is a by-product produced during the steelmaking process. Steelmaking slag is produced, for example, when iron is converted into steel in the Thomas process, the Linz-Donawitz process, the Siemens-Martin process or in an electric arc furnace. Steelmaking slag is produced when hot pig iron is treated with oxygen to remove carbon and other elements that have a higher affinity for oxygen than iron. The liquid slag is separated from the crude steel and cooled in pits or troughs to form crystallized or partially crystallized steelmaking slag. The cooled slag can then be crushed, ground and sieved to the desired fineness.

[0028] The steelmaking slag may be any slag produced in the steelmaking process. In particular, the steelmaking slag is any one of granulated blast furnace slag (GGBFS), basic oxygen furnace slag (BOS), ladle slag or electric arc furnace slag. According to a preferred embodiment, the steelmaking slag is ground granulated blast furnace slag. It is particularly preferred that the steelmaking slag, especially GGBFS, has a Blaine fineness of at least 4000 cm 2 / g, preferably at least 4500cm 2 / g, the glass content is at least 75%, the weight ratio of CaO+MgO / SiO2+Al2O3 is at least 1. Blaine fineness can be measured according to standard ASTM C204-18e1 or standard NF EN196-6.

[0029] In this article, clay mineral refers to a solid material composed of at least 30wt%, preferably at least 45wt%, and particularly at least 75wt% of clay minerals, each relative to dry weight. These clay minerals preferably belong to kaolinite (such as kaolinite, dickite, nacrite or halloysite), smectite (such as montmorillonite, nontronite or saponite), vermiculite, serpentine, palygorskite, sepiolite, chlorite, talc, pyrophyllite, mica (such as biotite, muscovite, illite, glauconite, green scale stone and polysilicon muscovite) or their mixtures. Clay minerals belonging to kaolinite (especially kaolinite) and mica (especially muscovite and illite) and their mixtures are particularly preferred. In this article, clay minerals can be any type of clay mineral, such as coarse clay, low temperature calcined clay or high temperature calcined clay. Coarse clay is a clay mineral extracted from, for example, a quarry, optionally purified and optionally dried. Low temperature calcined clay is clay that has been heat treated at a temperature of 500-1200°C. For example, low temperature calcined clay minerals can be produced in a rotary kiln or a flash calciner. High temperature calcined clay refers to clay minerals that have been heat treated at a temperature above 1200°C (usually between 1300-1400°C). High temperature calcined clay is usually crystalline or contains a large amount of crystalline phases, especially mullite.

[0030] In this article, the clay mineral is preferably a low-temperature calcined clay. Low-temperature calcined clay is a heat-treated clay material, and the heat treatment temperature is preferably between 500-1200°C, or a flash calcination process is performed between 800-1100°C. For example, a suitable flash calcination process is described in WO2014 / 085538. According to a particularly preferred embodiment of the present invention, the calcined clay is metakaolinite. Metakaolinite is a material formed by low-temperature calcination of kaolinite or a kaolinite-rich mineral, for example, with a kaolinite content of at least 30wt%, preferably at least 35wt%, relative to its dry weight. The calcination temperature for producing metakaolinite is generally in the range of 500-900°C.

[0031] The particle size of the aluminosilicate material of the present invention can be analyzed by sieve analysis, for example, the sieve analysis method described in standard ASTM C136 / C136M. This method is to pass the material through a number of sieves of different mesh sizes to separate fine particles from coarser particles. The material to be analyzed is passed through a series of successively decreasing sieves, vibrating using a single or combined horizontal, vertical or rotational motion. Thus, the percentage of particles retained on a sieve of a specific size can be obtained.

[0032] According to an embodiment, a suitable particle size D50 of the aluminosilicate material of the present invention is between 1 μm and 100 μm, preferably between 2 μm and 30 μm. The particle size D50 of a given material refers to the particle size that 50% of the particles of the material are larger than and 50% of the particles are smaller than. According to a specific embodiment, the particle sizes D10 and D90 of the aluminosilicate material of the present invention are both between 0.5 μm and 100 μm, preferably between 1 μm and 50 μm. The particle size D10 of a given material refers to the particle size that 90% of the particles of the material are larger than and 10% of the particles are smaller than, while the particle size D90 refers to the particle size that 10% of the particles are larger than and 90% of the particles are smaller than.

[0033] The standard for measuring the fineness of the aluminosilicate material of the present invention is the Blaine fineness. The Blaine fineness can be measured according to the standard ASTM C204-18e1 or the standard NF EN 196-6.

[0034] According to an embodiment, the aluminosilicate of the present invention, in particular the steelmaking slag, has a Blaine surface greater than 3000 cm 2 / g, preferably greater than 4000cm 2 / g, more preferably greater than 4500cm 2 / g, still more preferably greater than 5000cm 2 / g, especially greater than 6000cm 2 / g. Generally, the Blaine fineness of the aluminosilicate of the present invention is less than 12000cm 2 / g.

[0035] In this context, it is important that at least two chemically different aluminosilicates are used in the cementitious binder for the geopolymer. "Chemically different" means that the chemical composition of the individual aluminosilicates is different as determined by the XRF method described in EN 196-2:2013. Two chemically different aluminosilicates may be used in combination, or three chemically different aluminosilicates may be used in combination, or four or more chemically different aluminosilicates may be used in combination.

[0036] According to an embodiment, the at least two chemically different aluminosilicates are fly ash and steelmaking slag of Class F according to ASTM C618, in particular ground granulated blast furnace slag. Thus, according to an embodiment, the cementitious binder of the invention is characterized in that the at least two chemically different aluminosilicates are selected from steelmaking slag of Class F according to ASTM C618 and fly ash, the weight ratio of steelmaking slag to fly ash preferably being between 1.5:1 and 1:2, preferably between 1.3:1 and 1:1.5.

[0037] According to a further embodiment, the at least two chemically different aluminosilicates are fly ash class F according to ASTM C618, steelmaking slag (especially ground granulated blast furnace slag) and a clay mineral (preferably calcined clay, especially metakaolinite).

[0038] According to a further embodiment, in the cementitious binder of the invention, two chemically different aluminosilicates are present, which are selected from steelmaking slag, especially ground granulated blast furnace slag, and a clay mineral, preferably calcined clay, especially metakaolinite.

[0039] According to a further embodiment, the at least two chemically different aluminosilicates are fly ash of Class F according to ASTM C618 and a clay mineral, preferably calcined clay, in particular metakaolinite.

[0040] The use of at least two chemically different aluminosilicates, in particular a combination of fly ash of Class F according to ASTM C618 and ground granulated blast furnace slag, or a combination of fly ash of Class F according to ASTM C618, ground granulated blast furnace slag and calcined clay (in particular metakaolinite), or a combination of ground granulated blast furnace slag and calcined clay (in particular metakaolinite), improves the acid attack resistance of the cementitious binder for geopolymers or geopolymers according to the invention after hardening.

[0041] The at least two chemically different aluminosilicates are present in the geopolymer cementitious binder in an amount of not less than 30 wt %, preferably between 30 and 70 wt %, of the total dry weight of the cementitious binder. The weight percentages are relative to the sum of all aluminosilicates present.

[0042] In this context, ordinary Portland cement may be any cement conforming to ASTM C150. Ordinary Portland cement may also be cement of type CEM I or CEM II / AL, BL, A-LL, B-LL conforming to EN 197-1. Of course, equivalent cements made according to other standards (such as Japanese, Chinese or Indian standards) are also suitable. White Portland cement is also a suitable type of ordinary Portland cement.

[0043] The content of ordinary Portland cement present in the cement-based binder for geopolymers is not less than 20 wt %, preferably between 20 and 60 wt %, based on the total dry weight of the cement-based binder.

[0044] According to an embodiment, in the cement-based adhesive of the present invention, the weight ratio of ordinary Portland cement to the sum of at least two heat-activated aluminosilicates is between 0.1 and 2, preferably between 0.3 and 2, and more preferably between 0.6 and 1.6. In calculating this ratio, the sum of the weights of all heat-activated aluminosilicates is used.

[0045] The calcium sulfoaluminate cement (CSA cement) of the present invention is a cement containing clinker, wherein the clinker comprises C4 (A 3-x F x )$(C:CaO; A:Al2O3; F:Fe2O3; $:SO3), wherein x is an integer from 0 to 3. The CSA of the present invention generally comprises aluminates (CA, C3A, C 12 The CSA of the present invention comprises 15-75 wt% C4A3$, 0-10 wt% aluminates, 0-70 wt% belite, 0-35 wt% ferrite, 0-20 wt% ternesite and 0-20 wt% anhydrite, each based on the total dry weight of the CSA cement. For example, a suitable CSA can be purchased from HeidelbergCement AG, Buzzi Unicem, or from Caltra BV under the trade name Calumex.

[0046] The calcium aluminate cement (CAC) of the present invention is preferably a cement according to standard EN 14647:2006-01. However, the calcium aluminate cement of the present invention may also be an amorphous material consisting mainly of an amorphous calcium aluminate phase.

[0047] The calcium sulfate source may be any source of CaSO anhydrite (also referred to herein as anhydrous gypsum), CaSO α- and β-hemihydrates, and CaSO dihydrate. Examples of calcium sulfate sources are gypsum, phosphogypsum, and FGD-gypsum. It has been found that anhydrous gypsum performs best in the context of the present invention. Therefore, according to a preferred embodiment, in the cementitious binder of the present invention, the calcium sulfate source is anhydrous gypsum.

[0048] In the cementitious binder of the present invention, the weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is between 0.08 and 1.5, preferably between 0.3 and 1.1, more preferably between 0.5 and 1.1. When calculating this ratio, all calcium sulfate present in the cementitious binder must be taken into account. Calcium sulfate bound in the aluminate phase, especially in C4 (A 3-x F x )$, cannot be regarded as calcium sulfate in calculating this ratio. In calculating this ratio, all useful calcium aluminates and calcium sulfoaluminate phases contained in calcium sulfoaluminate cement or calcium aluminate cement must be taken into account. These useful phases are as described above, and particularly useful phases are C4(A 3-x F x )$, where x is an integer from 0 to 3, CA, C3A, C 12 A7, C2AF, and / or C4AF.

[0049] The weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is between 0.08 and 1.5, preferably between 0.3 and 1.1, more preferably between 0.6 and 1.1, which is very important for ensuring high dimensional stability of the geopolymer after hardening. High dimensional stability means in particular low autogenous or chemical shrinkage and even less expansion. The shrinkage or expansion used throughout the present invention is measured according to standard ASTM C157 / C157-M08.

[0050] As described above, according to an embodiment, two chemically different aluminosilicates are present in the cementitious binder of the present invention, the two aluminosilicates being selected from fly ash and steelmaking slag, particularly ground granulated blast furnace slag, Class F according to ASTM C618. In particular, in this embodiment, the presence of calcium sulfate and calcium sulfoaluminate and / or calcium aluminate in a specified weight ratio helps ensure that the geopolymer composition achieves the goal of resisting chemical attack after hardening.

[0051] According to an embodiment, the cementitious binder of the present invention further comprises 5-15 wt%, preferably 6-8 wt% silica fume, based on the total dry weight of the cementitious binder. The additional use of silica fume further improves the acid attack resistance of the geopolymer cementitious binder or geopolymer according to the present invention after hardening. In addition, it has also been found that the use of silica fume can improve the adhesion of the cementitious binder of the present invention or the geopolymer composition of the present invention during spraying concrete and / or in vertical or overhead applications.

[0052] According to an embodiment, the cementitious binder for geopolymers comprises or consists of (in each case relative to the total dry weight of the cementitious binder):

[0053] a) 30-70 wt % of a mixture of at least two chemically different aluminosilicates;

[0054] b) 20-60 wt% of ordinary Portland cement, and

[0055] c) 8-20 wt% of calcium sulfoaluminate cement or a mixture of calcium aluminate cement and a calcium sulfate source, wherein in the mixture, the weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is between 0.08-1.5, preferably 0.3-1.1, more preferably 0.6-1.1.

[0056] According to a particularly useful embodiment, the cementitious binder for geopolymers comprises or consists of (in each case, relative to the total dry weight of the cementitious binder):

[0057] a) not less than 30 wt% of a mixture of fly ash, class F according to ASTM C618, steelmaking slag (especially ground granulated blast furnace slag) and a clay mineral (preferably calcined clay, especially metakaolinite),

[0058] b) not less than 20 wt% of ordinary Portland cement,

[0059] c) 8-20 wt% of calcium sulphoaluminate cement or a mixture of calcium aluminate cement and a calcium sulphate source, wherein in the mixture, the weight ratio of calcium sulphate to calcium sulphoaluminate and / or calcium aluminate is between 0.08-1.5, preferably 0.3-1.1, more preferably 0.5-1.1, and

[0060] d) 5-15 wt%, preferably 6-8 wt% of silica fume.

[0061] According to a further particularly useful embodiment, the cementitious binder for geopolymers comprises or consists of (in each case relative to the total dry weight of the cementitious binder):

[0062] a) 40-50 wt% of a mixture of ground granulated blast furnace slag and a clay mineral, preferably calcined clay, in particular metakaolin,

[0063] b) 20-30 wt% of ordinary Portland cement, and

[0064] c) 14-20 wt% of calcium sulfoaluminate cement or a mixture of calcium aluminate cement and a calcium sulfate source, wherein in the mixture, the weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is between 0.08-1.5, preferably 0.3-1.1, more preferably 0.6-1.1.

[0065] According to an embodiment, in the cementitious binder of the present invention, silica fume, calcined clay and fly ash of Class F according to ASTM C618 are present, and the weight ratio of the sum of silica fume and calcined clay to fly ash is between 0.1 and 0.5. Therefore, the sum of silica fume and calcined clay refers to the combined weight of silica fume and calcined clay present in the composition.

[0066] The cementitious binder or geopolymer used in the geopolymer of the present invention preferably does not contain any alkali silicates, in particular does not contain sodium silicate or potassium silicate.

[0067] In a second aspect, the present invention relates to a geopolymer composition comprising

[0068] a) the above cement-based adhesive,

[0069] b) aggregates and / or fillers,

[0070] c) Optional other additives.

[0071] Aggregate can be any material that does not react in the hydration reaction of the hydraulic binder. Aggregate can be any aggregate commonly used in cementitious compositions. For example, typical aggregates include rock, crushed stone, gravel, sand, in particular quartz sand, river sand and / or artificial sand, recycled concrete, glass, expanded glass, hollow glass beads, glass ceramics, perlite, vermiculite, quarry waste, raw soil, burnt soil or molten soil or clay, porcelain, fused or sintered abrasives, firing supports, silica xerogels or bio-based aggregates (such as plant materials). Fillers are fine aggregates. Fillers are especially ground limestone, ground dolomite and / or ground aluminum oxide.

[0072] Sand is a particularly preferred aggregate. Sand is a naturally occurring granular material consisting of finely divided rock or mineral particles. It has various shapes and sizes. Examples of suitable sands are quartz sand, limestone sand, river sand or crushed aggregate. For example, standards ASTM C778 or EN 196-1 describe suitable sands.

[0073] Other additives may be any other additives common in the mortar and / or concrete industry, such as plasticizers and / or superplasticizers, air entraining agents, defoamers, stabilizers, rheology modifiers, in particular thickeners, water reducers, accelerators, retarders, shrinkage reducers, activators, promoters, water retarder, strength enhancing additives, fibers, dust removers, foaming agents, pigments, corrosion inhibitors, biocides and / or chromium (VI) reducing agents. In a cementitious composition, it is very advantageous to use two or more of the above additives in combination. In particular, thickeners, superplasticizers, accelerators and retarders.

[0074] According to an embodiment, the further additives are selected from lithium carbonate, alkali silicates, in particular sodium silicate or potassium silicate, citric acid, tartaric acid, sugars, sugar acids, sugar alcohols, aluminum sulfate, modified cellulose, organosilanes, ethylene glycol, magnesium oxide, calcium oxide, calcium silicate hydrate, phosphates, polycarboxylic acid ethers, naphthalene sulfonates, lignin sulfonates and / or melamine formaldehyde condensates.

[0075] According to an embodiment, the geopolymer composition of the present invention comprises the above-mentioned cement-based binder, aggregates and / or fillers and other additives, the cement-based binder is used in an amount of 20-60wt%, preferably 30-45wt%; the aggregates and / or fillers are used in an amount of 40-70wt%, preferably 50-65wt%; the other additives are used in an amount of 0-10wt%, preferably 0.1-5wt%, in each case relative to the total dry weight of the geopolymer composition.

[0076] According to an embodiment, the geopolymer composition of the invention is a dry composition. A dry composition is understood to mean a composition having a water content lower than 5 wt%, preferably lower than 1 wt%, relative to the total weight of the composition.

[0077] The dry geopolymer composition of the present invention can be mixed with water. The geopolymer composition starts to set and harden after contact with water. A suitable weight ratio of water to cement-based binder in the geopolymer composition is between 0.2-0.7, preferably between 0.3-0.5.

[0078] According to an embodiment, the geopolymer composition of the present invention is a wet geopolymer composition. The wet geopolymer composition comprises:

[0079] a) the above cement-based adhesive;

[0080] b) aggregates and / or fillers;

[0081] c) optional other additives;

[0082] d) Water, in an amount to achieve a weight ratio of water to cementitious binder of between 0.2 and 0.7, preferably between 0.3 and 0.5.

[0083] All preferred embodiments described above also pertain in this regard.

[0084] The cementitious binders of the present invention and geopolymers based on such binders can be used in a variety of construction methods.

[0085] In another aspect, the present invention relates to a method for repairing a concrete or mortar structure or masonry, the method comprising the steps of:

[0086] a) providing the above-mentioned cement-based adhesive or the above-mentioned geopolymer composition;

[0087] b) mixing the cementitious binder or geopolymer composition provided in step a) with water;

[0088] c) applying the mixture obtained in step b) to the surface of a hardened concrete or mortar structure; and

[0089] d) optionally hardening the applied mixture.

[0090] The mixing in step b) can be accomplished by any means known to the skilled person. For example, the mixing can be accomplished by means of a hand-held blender, a Hobart mixer, a mixing drum, a paddle mixer, a jet mixer, a screw mixer, a spiral mixer, a horizontal single-shaft mixer, a twin-shaft paddle mixer, a vertical shaft mixer, a ribbon blender, an orbital mixer, a can-changing mixer, a vertical stirring chamber, or an air agitation operation. The mixing can be performed continuously, semi-continuously, or in batches. Continuous mixing has the advantage of a large material throughput.

[0091] In step c), the application can be carried out in any manner known to those skilled in the art. According to a specific embodiment, the mixture is applied in step c) by means of a trowel, a brush or a roller. According to other embodiments, the mixture is applied in step c) by means of a spraying device. The advantage of spraying is that the application can be carried out very quickly and continuously. Suitable spraying devices are known to those skilled in the art. In step c), the mixture can be applied in different thicknesses according to actual needs. It is also possible to apply the mixture in step c) in a way that fills holes or cracks.

[0092] The hardening in step d) is usually done under ambient conditions. Thus, according to an embodiment, the hardening is carried out at a temperature between 5-35°C and a pressure of about 1023 mbar. According to other embodiments, the hardening is done at elevated temperatures, for example at a temperature above 40°C, and up to 100°C or 120°C.

[0093] According to an embodiment, the repair method of concrete or mortar structure or masonry is a method that complies with the principles of standard EN 1504-9: 2008. In particular, according to standard EN 1504-9: 2008, the repair method of concrete or mortar structure or masonry is a method that complies with principle 2 (especially 2.2), principle 3 (especially 3.1 and 3.3), principle 4 (especially 4.4, 4.5, 4.6), principle 5 (especially 5.1 and 5.3), principle 6, principle 7 (especially 7.1) or principle 8 (especially 8.2).

[0094] In particular, the method of repairing concrete or mortar structures or masonry of the present invention is suitable for use in environments in contact with corrosive chemicals, particularly aqueous acid solutions, sulfates, chlorides and / or salt water.

[0095] In another aspect, the present invention relates to a method for protecting a structure, in particular a method for protecting a concrete or mortar structure or a masonry structure, the method comprising the following steps:

[0096] a) providing the above-mentioned cement-based adhesive or the above-mentioned geopolymer composition;

[0097] b) mixing the cementitious binder or geopolymer composition provided in step a) with water;

[0098] c) applying the mixture obtained in step b) to the surface of a hardened structure; and

[0099] d) optionally hardening the applied mixture.

[0100] In particular in the method of protecting a structure, mixing, applying and curing can be carried out in the manner described above.

[0101] In the protection method of the present invention, the structure to be treated can be a long-term dry structure, a frequently wet structure (e.g., a wet room) or a structure in contact with water for a long time. For example, the structure to be treated can be the following parts (e.g., floors, walls and / or ceilings): balconies, bathrooms, kitchens, swimming pools, port structures, water pipes, water tanks, sewer structures, sewer pipes, manholes, lift stations, pumping stations, collectors, wastewater treatment plants, coastal areas or bridge decks.

[0102] In particular, the structure protection method of the present invention is particularly suitable for environments in contact with corrosive chemicals, especially acid aqueous solutions and / or salt water.

[0103] In another aspect, the present invention relates to a method for waterproofing a structure, in particular a method for waterproofing a concrete or mortar structure or a masonry structure, the method comprising the following steps:

[0104] a) providing the above-mentioned cement-based adhesive or the above-mentioned geopolymer composition;

[0105] b) mixing the cementitious binder or geopolymer composition provided in step a) with water;

[0106] c) applying the mixture obtained in step b) to the surface of a hardened structure; and

[0107] d) optionally hardening the applied mixture.

[0108] Particularly in the method of waterproofing a structure, mixing, applying and hardening may be carried out in the above-described manner.

[0109] The term "waterproof" in the context of the present invention includes both waterproofing and moisture-proofing as defined in ACI 515.1R-85.

[0110] In the waterproofing method of the present invention, the structure to be treated may be a long-term dry structure, a frequently wet structure (e.g., a wet room) or a structure in contact with water for a long time. For example, the structure to be treated may be the following parts (e.g., floors, walls and / or ceilings): balconies, bathrooms, kitchens, swimming pools, port structures, water pipes, water tanks, sewer structures, sewer pipes, manholes, lift stations, pumping stations, collectors, wastewater treatment plants, coastal areas or bridge decks.

[0111] The structural waterproofing method of the present invention is particularly suitable for environments in contact with corrosive chemicals, especially acid aqueous solutions and / or salt water.

[0112] In another aspect, the present invention relates to a method for three-dimensional printing of a mortar composition, the method comprising the following steps

[0113] a) providing the above-mentioned cement-based adhesive or the above-mentioned geopolymer composition;

[0114] b) mixing the cementitious binder or geopolymer composition provided in step a) with water,

[0115] c) selectively delivering the mixture obtained in step b) to a print head, preferably a print head mounted on a movable arm,

[0116] c) applying the mixture obtained in step b) layer by layer from a printing head to form a three-dimensional object, and

[0117] d) Selectively hardening three-dimensional objects.

[0118] According to a preferred embodiment, in the 3D printing method of the present invention, a cement-based binder or a geopolymer composition is used, wherein two chemically different aluminosilicates are selected from steelmaking slag (especially ground granulated blast furnace slag) and clay minerals (preferably calcined clay, especially metakaolinite). In the cement-based binder for geopolymers used in the 3D printing method, the weight ratio of steelmaking slag (especially ground granulated blast furnace slag) to clay minerals (preferably calcined clay, especially metakaolinite) is preferably 2:1 to 5:1, especially 3.5:1. In addition, in the cement-based binder for geopolymers used in the 3D printing method, the total amount of clay minerals (preferably calcined clay, especially metakaolinite) is preferably not more than 20wt%, preferably not more than 16wt%, and more preferably not more than 11wt%. In particular, excessive use of metakaolinite may result in poor extrusion effect and increased pressure during extrusion. In addition, fly ash may also be present.

[0119] In particular, in the 3D printing method of the mortar composition, mixing, applying and hardening can be carried out in the above-mentioned manner.

[0120] In particular, the 3D printing method of the mortar composition can be performed by the device described below. Therefore, any features related to the device below can be implemented in the above method accordingly.

[0121] According to an embodiment, the device for producing three-dimensional objects in the method of the present invention, in particular a robotic system, includes a supply device for a cement-based adhesive or a geopolymer composition mixed with water, a supply pipeline for supplying the cement-based adhesive or the geopolymer composition mixed with water to a print head, a mixing unit and a control unit.

[0122] The mixing unit is preferably a static and / or dynamic mixer, arranged downstream of the supply unit and upstream of the outlet nozzle. In particular, the mixing unit is arranged so that the cementitious binder or geopolymer composition mixed with water is mixed before entering the supply line, while passing through the supply line and / or after leaving the supply line.

[0123] The device comprises a print head, which is preferably movable in at least one spatial direction to form a three-dimensional structure. The print head has a print head outlet, in particular an outlet nozzle, for applying a cementitious binder or a geopolymer component mixed with water. If necessary, the print head can include a controllable outlet, in particular in the form of an outlet nozzle that can be opened and closed. In this case, the outlet nozzle that can be opened and closed is preferably controllable by a control unit.

[0124] According to an embodiment, the device comprises at least one mixer, in particular a static and / or dynamic mixer, which is arranged downstream of the supply unit for adding additives to the cementitious binder or geopolymer composition mixed with water. In particular, the at least one mixer is arranged between (i) the print head outlet, in particular the outlet nozzle, and (ii) the supply unit and the inlet nozzle for adding additives to the cementitious binder or geopolymer composition mixed with water. In another preferred embodiment, the device comprises an additive supply unit, optionally with an additive inlet nozzle, which is configured to add additives to the cementitious binder or geopolymer composition mixed with water in the print head, the mixing device and / or the supply line upstream of the print head.

[0125] According to an embodiment, a control unit of the device includes a processor, a storage unit, and a plurality of interfaces for receiving data and a plurality of interfaces for controlling various components of the device.

[0126] Figure 1 An exemplary system 1 for implementing a 3D printing method according to the present invention is schematically shown.

[0127] The system 1 comprises a mobile device 2 with a movable arm 2.1. The print head 3 is mounted at the free end of the arm 2.1 and can be moved in all three spatial dimensions by the arm 2.1. This allows the print head 3 to be moved to any position within the working area of ​​the mobile device 2.

[0128] Internally, the print head 3 has a tubular channel 3.1, from the end surface facing the arm 2.1 ( Figure 1 The top of the channel 3.1 extends to the opposite and free end face for conveying a mixture of cement-based material and water. At the free end, the channel 3.1 leads to a controllable outlet 4 in the form of a nozzle, which can be opened and closed continuously.

[0129] According to some embodiments, an inlet nozzle 5 for adding additives opens laterally into the channel 3.1 in the area facing the arm 2.1. Through the inlet nozzle 5, additives such as rheological additives can be added as required to the mixture of cementitious material and water moving through the channel 3.1.

[0130] According to an embodiment, inside the print head 3, downstream with respect to the inlet nozzle, a static mixer 6 is installed in the channel 3.1, which additionally mixes the mixture of cementitious material and water with optional additives.

[0131] In the region of the controllable outlet 4, a measuring unit 8 can be arranged for determining the pressure in the tubular channel 3.1. The sampling rate of the measuring unit 8 is, for example, 10 Hz.

[0132] According to some embodiments, a device 7 for degassing the mixture of cement-based material and water is also attached to the print head 3. The device is designed as a vacuum processing device, so that it can reduce the air content in the mixture of cement-based material and water. To this end, for example, a section of the wall of the channel 3.1 can be designed as a breathable membrane, so that air is extracted from the mixture of cement-based material and water by evacuating the outside of the channel 3.1.

[0133] The system 1 for applying a mixture of cementitious material and water has a feed device 9, the input of which corresponds to containers 11.1, 11.2 and optionally 11.3 and 11.4. Container 11.1 is filled with a first component, which is a cementitious composition for geopolymers or a geopolymer composition according to the invention. A second container 11.2 is filled with a second component, which consists of water. A third component is optional. In the optional additive storage tank 11.4, for example, a rheological additive is optionally present.

[0134] On the output side, the feed device 9 has at least two, optionally three, independent outlets, each of which is connected to one of the inlets 10.1, 10.2, and optionally 10.3 of the mixing device 10. The feed device 9 also has individually controllable metering devices ( Figure 1 11.1, 11.2 and optionally 11.3 and 11.4) so ​​that the various components can be metered individually into the mixing device 10.

[0135] According to the embodiment, the mixing device 10 can be designed as a static mixer or a dynamic mixer, preferably a continuous dynamic mixer, and can also include an integrated conveying device in the form of a screw conveyor. In the mixing device, the separately metered components are mixed together and conveyed to a flexible pipeline 12 connected to the outlet side of the mixing device.

[0136] The mixture of cement-based material and water can be conveyed into the print head 3 via a flexible line 12 which opens into a tubular channel 3 . 1 at the end of the print head facing the arm 2 . 1 and is continuously applied via the controllable outlet 4 .

[0137] As part of the system 1, a measuring unit 13 is optionally installed, which is installed in the transport line 12 in the area between the mixing device 10 and the print head 3. The measuring unit comprises, for example, an ultrasonic sensor for determining the flow characteristics of the cementitious material and water mixture. The sampling rate of the measuring unit 13 is, for example, 10 Hz.

[0138] The central control unit 14 of the system 1 includes a processor, a storage unit, a plurality of interfaces for receiving data, and a plurality of interfaces for controlling various components of the system 1 .

[0139] In this respect, the mixing device 10 is connected to the control unit 14 via a first control line 15a, while the feed device is connected to the control unit 14 via a second control line 15b. Thus, the various components in the containers 11.1, 11.2 and optionally 11.3 can be metered into the mixing device 10 by the central control unit according to a predetermined recipe stored in the control unit and delivered to the flexible pipeline 12 at an adjustable delivery rate.

[0140] The controllable outlet 4, the inlet nozzle 5, and the optional device 7 for degassing the mixture of cementitious material and water at the print head are also connected to the control unit 14 via separate control lines 15c, 15d, 15e, respectively, and can be controlled or monitored by the latter.

[0141] The moving device 2 is also connected to the control unit 14 via another control line 15g. This means that the movement of the print head 3 can be controlled by the control unit 14.

[0142] The measuring unit 8 (if any) is connected to the control unit 14 via the data line 15 h so that the printing data recorded in the measuring unit is transmitted to the control unit 14 .

[0143] Likewise, the measuring unit 13 (if any) is connected to the control unit 14 via a data line 15 f so that the flow characteristic data recorded in the measuring unit is transmitted to the control unit 14 .

[0144] In another aspect, the present invention relates to a method for spraying concrete, said method comprising the steps of

[0145] a) providing the above-mentioned cement-based adhesive or the above-mentioned geopolymer composition,

[0146] b) mixing the cementitious binder or geopolymer composition provided in step a) with water,

[0147] c) conveying the mixture obtained in step b) into a spray gun,

[0148] d) optionally mixing an additional accelerator into the mixture obtained in step b),

[0149] c) spraying the mixture from the spray gun into cavities and / or surfaces,

[0150] d) optionally hardening the mixture.

[0151] According to an embodiment, the additional accelerator added in step d) is an accelerator for sprayed concrete, in particular a composition based on aluminum sulfate.

[0152] Preferably, the composition based on aluminum sulfate is added to the mixture prepared in step b) during delivery or in a lance.

[0153] Suitable spray guns for spraying the mixture in step c) are known to the skilled person. Suitable spray guns are, in particular, conventional spray guns for shotcrete (also called sprayed concrete), preferably with a nozzle.

[0154] According to an embodiment, in the shotcrete method according to the invention, a substrate is coated. In particular, the substrate is the surface of a tunnel, a mine, an excavation site, a bay, a well and / or a drain. According to a further embodiment, in the shotcrete method according to the invention, a cavity is filled. According to a further embodiment, in the shotcrete method according to the invention, a free-form structure is being built.

[0155] number

[0156] Figure 1 Mortar composition 3D printing system

[0157] 1Mortar composition 3D printing system

[0158] 2 Mobile Devices

[0159] 2.1 Movable Arm

[0160] 3 Print head

[0161] 3.1 Channels

[0162] 4. Export

[0163] 5 Inlet nozzle

[0164] 6 Static mixer

[0165] 7 Degassing device

[0166] 8 Measuring units

[0167] 9 Feeding device

[0168] 10 Mixing device

[0169] 10.1-10.3 Entrance

[0170] 11.1-11.4 Containers

[0171] 12 Flexible pipeline

[0172] 13 Measurement units

[0173] 14 Control Unit

[0174] 15a-15h control line, data line Example

[0175] Table 1 below summarizes the chemical compositions of some of the raw materials used.

[0176] Table 1: Chemical composition and fineness of fly ash, ground granulated blast furnace slag, metakaolinite and silica fume used

[0177]

[0178] * According to XRF determination as described in EN 196-2:2013

[0179] **#325 mesh retention

[0180] Type I white ordinary Portland cement (w-PC) with a Blaine fineness of 4280 cm2 / g produced by Royal White Cement was used.

[0181] Calcium sulphoaluminate cement (CSA) was used in which the C4A3$ content was 69.4wt%, the anhydrous gypsum content was 2.6wt% and the C2S content was <25wt%.

[0182] The calcium sulfate used is anhydrite.

[0183] The sand used was a silica sand mixture with a particle size of 0.1-2.5 mm.

[0184] The fine filter used was ground feldspar with an average particle size of 45 microns.

[0185] The additive used was a polycarboxylate ether (PCE) of type Melflux 6681 supplied by Azelis Americas Inc.

[0186] Example 1 - Geopolymer Testing

[0187] To prepare the cementitious binder or geopolymer formulation for geopolymers, the dry ingredients were weighed into a Hobart mixer in the amounts shown in Tables 2-5 below and mixed for 3 minutes at 23°C and 50% relative humidity. Water was then added to achieve the weight ratio of cementitious binder to water (ratio w / b) shown in Tables 2-5 below and mixing continued for 3 minutes. Test specimens were cast directly from the resulting geopolymer compositions.

[0188] The measurement was performed as follows.

[0189] Shrinkage is measured after curing for 24 hours at 23°C / 50% rh according to standard ASTM C157 / C157-M08. Shrinkage of less than or equal to 1500 μm / m is desirable. In this context, expansion (indicated by positive values ​​in the following tables 2-5) is preferred to shrinkage.

[0190] The compressive strength (referred to as CS in Tables 2-5 below) was determined according to standard ASTM C109 / C109M using a cylinder with a height of 25.4 mm and a diameter of 25.4 mm. The compressive strength was measured after curing the test specimens at 23°C / 90% rh for 7 days and then immersed in tap water for 7 days.

[0191] Acid resistance (referred to as AR in Tables 2-5 below) was measured by comparing the compressive strength of the test specimens. For comparison, a first specimen was prepared from each mix according to ASTM C109 / C109M as described above. A second specimen of each mix was prepared according to the same procedure, but instead of curing the second specimen at 23°C / 90% rh for 7 days and then soaking in tap water for 7 days, the second specimen was cured at 23°C / 90% rh for 7 days and then soaked in 0.5M sulfuric acid for 7 days. The difference in compressive strength of the two test specimens has been calculated and is reported as a percentage as follows (negative values ​​represent a loss in compressive strength when stored in acid, and positive values ​​represent an increase in compressive strength when stored in acid).

[0192] For ease of reference, the following Tables 2-5 list the weight ratios of calcium sulfate and calcium sulfoaluminate (ratio C$:CSA) in each mixture.

[0193] Compositions C-1 to C-9 are not according to the invention and are included for comparison purposes. Compositions G-1 to G-13 are according to the invention.

[0194] Table 2: Comparative mixtures from C-1 to C-8 and results

[0195]

[0196]

[0197] *23 parts potassium silicate solution (47% solids) was used

[0198] nd: Undetermined

[0199] na: unknown

[0200] As can be seen from the above examples, geopolymer compositions according to the teaching of Davidovits (C-1) do result in good strength and acid resistance, but also show very high shrinkage. Using a Portland cement-based binder reduces shrinkage, but also reduces acid resistance (Examples C-2 to C-4). The simultaneous use of Portland cement, CSA, and calcium sulfate without aluminosilicate also results in acceptable shrinkage, but low acid resistance. Interestingly, the use of only one aluminosilicate with Portland cement, CSA, and calcium sulfate-based binders is not sufficient to produce high strength and simultaneously improve acid resistance (see Examples C-6 and C-7).

[0201] Using only CSA without acid anhydride will indeed reduce the shrinkage, but will not achieve the desired acid resistance.

[0202] Table 3: Geopolymer mixtures G-1 to G-6 and results

[0203] G-1 G-2 G-3 G-4 G-5 G-6 FA[g] 11 13 13 13 13 10 GGBS[g] 14 12 12 12 12 12 w-PC[g] 9 10 10 10 10 10 MK[g] 1.5 SF[g] 1 CSA[g] 3.6 5.9 4.8 4 4.4 4 <![CDATA[CaSO4[g]]]> 1.6 1.3 0.8 1.5 1.2 1.7 Sand[g] 58.7 55.7 57.3 57.4 57.4 57.7 Filler[g] 2 2 2 2 2 2 PCE[g] 0.1 0.1 0.1 0.1 0.1 0.1 Ratio C$:CSA 0.68 0.36 0.28 0.58 0.43 0.65 Ratio w / b 0.39 0.39 0.39 0.39 0.39 0.39 Shrinkage rate [μm / m] na -1050 -1400 +800 na na CS[psi] 4710 na na 5537 5344 5905 AR[%] -13.8 na na -20.9 -16.7 na

[0204] na: unknown

[0205] From the results in Table 3 it can be seen that combining at least two chemically different aluminosilicates with binders based on Portland cement, CSA and calcium sulfate can both improve acid resistance and show low shrinkage.

[0206] In addition, as the weight ratio of calcium sulfate to calcium sulfoaluminate increases, the shrinkage improves (Examples G-2 to G-4).

[0207] Partial replacement of fly ash with metakaolin and silica fume additionally improves acid resistance.

[0208] Table 4: Geopolymer mixtures G-7 to G-9 and results

[0209] G-7 G-8 G-9 G-10 FA[g] 13 13 13 14 GGBS[g] 12 12 12 9 w-PC[g] 10 10 10 11 CSA[g] 4 4 4 4.3 <![CDATA[CaSO4[g]]]> 1.3 1.5 1.7 1.9 Sand[g] 55.6 57.4 57.2 57.7 Filler[g] 2 2 2 2 PCE[g] 0.1 0.1 0.1 0.1 Ratio C$:CSA 0.51 0.58 0.65 0.67 Ratio w / b 0.37 0.37 0.37 0.39 Shrinkage rate [μm / m] -850 -800 +100 na CS[psi] 4425 4305 3805 4017 AR[%] na na na -4.9

[0210] na: unknown

[0211] As can be seen from the results in Table 4 above, as the weight ratio of calcium sulfate to calcium sulfoaluminate increases, the shrinkage rate improves (Examples G-7 to G-9).

[0212] Furthermore, by comparing the results of Table 3 and Table 4 (see Examples G-1 and G-10), it can be seen that increasing the weight ratio of GGBS to fly ash increases strength but decreases acid resistance. However, it must be noted that the acid resistance of these examples in both tables is acceptable.

[0213] Table 5: Comparison of mix C-9 and geopolymer mixes G-10 to G-13 and results

[0214]

[0215]

[0216] na: unknown

[0217] As can be seen from the results in Table 5, the shrinkage of the composition according to the present invention is significantly reduced and the compressive strength is significantly improved compared to the reference. Compared with the binder with the combination of GGBS and metakaolinite, the binder with the combination of GGBS and fly ash has a lower shrinkage, but also a slightly lower compressive strength (see Examples G-10 and G-11). Adding additional silica fume can further reduce the shrinkage and improve the compressive strength and acid resistance (see Examples G-13 and G-10). Balancing the ratio of GGBS to fly ash can also further reduce the shrinkage and improve the acid resistance (see Examples G11 and G-12).

[0218] Example 2 - 3D Printing

[0219] use Figure 1 The system 3D prints a geopolymer composition. The width of the applied material layer is 5 cm and the height is 0.5 cm. The geopolymer composition consists of the following (raw materials as described above): 16.3 wt% GGBS, 9.4 wt% w-PC, 2 wt% MK, 5.8 wt% CSA, 0.5 wt% CaSO4, 43 wt% sand, 16.7 wt% ground CaCO3 (D50: about 30 μm), 5 wt% CaCO3 fine filler (D50: 0.8 μm), 0.2 wt% PCE and 1.1 wt% additives (a mixture of diutan gum and modified cellulose thickener, gluconate and aluminum sulfate). The weight ratio of water to powder used is 0.16.

[0220] Visual inspection showed good printability, in particular: very limited droop and no run between the layers, good adhesion between the layers, and at least three layers could be applied on top of each other. The time required to print a 20 cm high object was 13 minutes. The initial hose pressure was 200 psi and the final hose pressure was 260 psi. Thus, the geopolymer composition produced according to the present invention showed smooth extrusion and excellent finish.

[0221] The 24-hour and 28-day strengths of the printed objects were both high and surprisingly higher than those of objects printed using conventional cement-based 3D printing inks.

Claims

1. A cementitious binder for geopolymers, said cementitious binder comprising, in each case relative to the total dry weight of said cementitious binder: a) not less than 30 wt. % of a mixture of at least two chemically different aluminosilicates, b) not less than 20 wt% of ordinary Portland cement, and c) 8-20 wt% of calcium sulfoaluminate cement or a mixture of calcium aluminate cement and a calcium sulfate source, wherein in the mixture, the weight ratio of calcium sulfate to calcium sulfoaluminate and / or calcium aluminate is 0.08-1.5, preferably 0.3-1.1, more preferably 0.6-1.

1.

2. The cementitious binder of claim 1, wherein the at least two chemically different aluminosilicates are selected from steelmaking slag and fly ash of Class F according to ASTM C618, preferably the weight ratio of steelmaking slag to fly ash is from 1.5:1 to 1:2, preferably from 1.3:1 to 1:1.

5.

3. The cementitious binder of claim 1, wherein the first aluminosilicate is steelmaking slag and the other aluminosilicates are selected from fly ash and / or calcined clay of Class F according to ASTM C618.

4. A cementitious binder as claimed in claim 1, wherein two chemically different aluminosilicates are present, selected from steelmaking slag, especially ground granulated blast furnace slag, and a clay mineral, preferably calcined clay, especially metakaolinite.

5. A cementitious adhesive as claimed in any one of the preceding claims, wherein The cement-based adhesive further comprises 5-15 wt%, preferably 6-8 wt%, of silica fume relative to the total dry weight of the cement-based adhesive.

6. A cement-based binder as claimed in any one of the preceding claims, wherein the weight ratio of ordinary Portland cement to the sum of the at least two thermally activated aluminosilicates is 0.1-2, preferably 0.3-2, more preferably 0.6-1.

6.

7. The cementitious binder as claimed in claim 1, wherein silica fume, calcined clay and fly ash of Class F according to ASTM C618 are present, wherein the weight ratio of the sum of silica fume and calcined clay to fly ash is 0.1-0.

5.

8. The cement-based binder according to any one of claims 2 to 7, wherein the steelmaking slag is ground granulated blast furnace slag.

9. The cementitious binder of any one of the preceding claims, wherein the calcium sulfate source is anhydrite.

10. Geopolymer composition comprising a) a cement-based adhesive as claimed in any one of claims 1 to 9, b) aggregates and / or fillers, c) Optional other additives.

11. A method for repairing a concrete or mortar structure or a masonry structure, the method comprising the following steps: a) providing a cementitious adhesive according to claims 1 to 9 or a geopolymer composition according to claim 10; b) mixing the cementitious binder or the geopolymer composition provided in step a) with water; c) applying the mixture obtained in step b) to the surface of a hardened concrete or mortar structure; and d) optionally hardening the applied mixture.

12. A method for protecting a structure, in particular a method for protecting a concrete or mortar structure or a masonry structure, the method comprising the following steps: a) providing a cementitious adhesive according to claims 1 to 9 or a geopolymer composition according to claim 10; b) mixing the cementitious binder or the geopolymer composition provided in step a) with water; c) applying the mixture obtained in step b) to the surface of the hardened structure; d) optionally hardening the applied mixture.

13. A method for waterproofing a structure, in particular a method for waterproofing a concrete or mortar structure or a masonry structure, the method comprising the following steps: a) providing a cementitious adhesive according to claims 1 to 9 or a geopolymer composition according to claim 10; b) mixing the cementitious binder or the geopolymer composition provided in step a) with water; c) applying the mixture obtained in step b) to the surface of a hardened structure; and d) optionally hardening the applied mixture.

14. A 3D printing method for a mortar composition, the method comprising the following steps: a) providing a cementitious adhesive according to claims 1 to 9 or a geopolymer composition according to claim 10; b) mixing the cementitious binder or the geopolymer composition provided in step a) with water; c) optionally conveying the mixture obtained in step b) to a print head, preferably a print head mounted on a movable arm, c) applying the mixture obtained in step b) layer by layer from a printing head to form a three-dimensional object, and d) optionally hardening the three-dimensional object.

15. A method for spraying concrete, the method comprising the following steps: a) providing a cementitious adhesive according to claims 1 to 9 or a geopolymer composition according to claim 10; b) mixing the cementitious binder or geopolymer composition provided in step a) with water; c) conveying the mixture obtained in step b) to a spray gun; d) optionally mixing an additional accelerator into the mixture obtained in step b); c) spraying the mixture from the spray gun into a cavity and / or onto a surface; and d) optionally hardening the applied mixture.

Citation Information

Patent Citations

  • Synthetic inorganic polymer of the silicoaluminate family and process for the preparation thereof; moulded articles containing this polymer, and process for their preparation

    EP0026687A2

  • Geopolymer compositions

    US20110271876A1

  • Dimensionally stable geopolymer composition and method

    WO2013163009A1

  • System for the production of fine lime

    WO2014085538A1